2004
DOI: 10.1191/0309133304pp409ra
|View full text |Cite
|
Sign up to set email alerts
|

Documenting catchment suspended sediment sources: problems, approaches and prospects

Abstract: Establishing catchment suspended sediment sources is fraught with difficulty. Data collection comprises indirect and direct approaches and an overview is provided. The indirect approach uses a range of techniques to measure or evaluate sediment mobilization. Yet, although recent technological advances in surveying, remote sensing and photogrammetry provide improved resolution of temporal and spatial patterns of catchment erosion, these procedures take no account of source -river connectivity and the uncertaint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
176
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(176 citation statements)
references
References 157 publications
(171 reference statements)
0
176
0
Order By: Relevance
“…when the transporting agent is more effective at carrying the sediment). The sequence of transport, deposition and remobilization has also been described as a sediment cascade (Collins and Walling, 2004;Fryirs, 2013;Harvey, 2002). In the following sections, the spatial and temporal dimensions of the sediment cascade are further discussed.…”
Section: Sediment Generation and Transport Towards The Rivermentioning
confidence: 99%
See 1 more Smart Citation
“…when the transporting agent is more effective at carrying the sediment). The sequence of transport, deposition and remobilization has also been described as a sediment cascade (Collins and Walling, 2004;Fryirs, 2013;Harvey, 2002). In the following sections, the spatial and temporal dimensions of the sediment cascade are further discussed.…”
Section: Sediment Generation and Transport Towards The Rivermentioning
confidence: 99%
“…A range of empirical models are used to analyze and quantify SS loads and sources in rivers and evaluate the importance of different drivers (Bilotta et al, 2012;Collins and Walling, 2004;Gao, 2008). While individually these models are useful for expressing SS transport for the process and scale under question, they typically address specific parts of the sediment cascade and are relevant to particular timescales.…”
Section: Empirical Approaches To Analyze Suspended Sediment Transportmentioning
confidence: 99%
“…The same principle can be applied to sediment source tracing, through a technique known as sediment fingerprinting (Collins et al, 1997;Collins and Walling, 2002;Collins and Walling, 2004). Source sediments are ascribed a source type e.g.…”
Section: Principal Components Analysismentioning
confidence: 99%
“…Sediment tracing techniques provide a direct method of determining sediment provenance (for reviews, please see: Collins and Walling, 2004;Davis and Fox, 2009;Guzman et al, 2013;Haddadchi et al, 2013;Koiter et al, 2013). Sediment tracing research has demonstrated that large dams reduce downstream migration of contaminated sediments (Lepage et al, 2016), that decontamination reduces downstream radiocesium transfers (Evrard et al, in review), and that alluvial soils, and the rice paddies occupying them, contribute disproportionately more sediment downstream relative to their spatial extent in the Fukushima region (Lepage et al, 2016).…”
Section: Introductionmentioning
confidence: 99%